Rekonstruksi Konsep Tauhid dalam Perspektif Filsafat: Pendekatan Epistemologis dan Ontologis - Ahmad Sahid, Toto; Maulana, Asror; Nurfaizah (CV Kalimasada Group, 2024)
Tawhid, as the core teaching of Islam, is the foundation of faith that underlies every aspect of religious belief and practice. Within a philosophical framework, Tawhid is not only understood normatively-theologically but can also be analyzed through two main dimensions: epistemology and ontology. Tawhid epistemology focuses on how knowledge about the oneness of God is obtained, including revelation, reason, and spiritual experience as the main means by which humans understand God. Meanwhile, Tawhid ontology explores the nature of God's existence as an absolute entity and his relationship with the universe as creation. This research aims to integrate epistemological and ontological perspectives in understanding Tawhid, using qualitative methods based on philosophical analysis. Data was collected from primary sources such as the Koran, Hadith, as well as the works of classical Islamic philosophers such as Al-Farabi, Ibn Sina, Al-Ghazali, and Mulla Sadra, combined with secondary sources in the form of contemporary studies. Research findings show that Tawhid is not only a theological principle but also a paradigm that connects human knowledge with the reality of existence. Tawhid in a philosophical perspective opens up space for synthesis between revelation and reason, making it a comprehensive and relevant basis for thinking to answer modern intellectual challenges. This contribution strengthens the integration between Islamic philosophy and theology, providing a solid conceptual basis for a deeper study of Islam.